Cherry‐picking of evidence fails to accurately show extent of overdiagnosis: Mammographic screening harms understated. Issue 2 (14th May 2013) - Woolley, Emma
<x xml:space="preserve">Abstract</x> The article by Lee and Peters (2013) clearly demonstrated bias which is inherent when staff of a program reviews the efficacy of their own program. It takes great bravery and humility to accept that a program which has received as much financial and political investment as BreastScreen Australia might be doing more harm than good. Had Lee and Peters reviewed all of the current evidence on overdiagnosis, the picture painted by the review would have been quite different. <boxed-text content-type="graphic" id="jmrs13-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>